THE QUALITY OF POPULATION ADMINISTRATION AND CIVIL REGISTRATION SERVICES AT THE OFFICE OF THE POPULATION AND CIVIL REGISTRATION OFFICE SOUTH BENGKULU - Rozi Febrizal; Harmiati; Heru Purnawan (Yayasan Wayan Marwan Pulungan, 2023)
Public service is an activity carried out by an agency/organization within an agency that will be used as an effort to meet the needs of the community. Purpose: this research is to determine the quality of Population Administration and Civil Registry services at the South Bengkulu Population and Civil Registration Service (Dindukcapil). Method : This type of research uses a qualitative descriptive method. The instrument in this research is the researcher himself. Data collection techniques using observation techniques and interview techniques. The informant selection technique used purposive sampling method. Data analysis techniques with Data Reduction, Data Presentation and Conclusion Drawing. Research Results: Researchers used five aspects of public service quality, namely physical evidence (Tangible) of the South Bengkulu Population and Civil Registration Service (Dindukcapil), services still need to improve physical facilities and completeness of adequate facilities and infrastructure, Reliability, the people of South Bengkulu are satisfied with the services provided by the South Bengkulu Population and Civil Registration Service (Dindukcapil), the Responsiveness of the South Bengkulu Population and Civil Registration Service (Dindukcapil) serves the community well, with mutual communication between officers and the community, Assurance if the management of services at the South Bengkulu Population and Civil Registration Office (Dindukcapil) is easy and Empathy (Empathy) The concern of employees to always prioritize the needs of the community will support the creation of Quality Integrated services. Conclusion: Administrative services at the South Bengkulu Population and Civil Registration Office (Dindukcapil) are not yet qualified.